Intramuscular vitamin A injection in newborn lambs enhances antioxidant capacity and improves meat quality - Song, Pengkang; Huo, Guoqiang; Feng, Jinxin; Zhang, Weipeng; Li, Xuying; Zhao, Junxing (Frontiers in Veterinary Science, 2023)
Vitamin A (VA) and its metabolite, retinoic acid (RA) possess several biological functions. This report investigated whether neonatal intramuscular VA injection affected antioxidative activity and meat quality in longissimus dorsi (LD) muscle of lambs. Lambs were injected with 0 (control) or 7,500 IU VA palmitate into the biceps femoris muscle on day 2 after birth. At 3, 12 and 32 weeks of age, blood samples were collected in the jugular vein for serum levels of RA and muscle samples were collected in the biceps femoris for analysis of relative mRNA expression of enzyme contributors to retinoid metabolism. All animals were harvested at 32 weeks of age and muscle samples were collected to explore the role of VA on the meat quality and antioxidant capacity of lambs. Our results indicated that VA increased the redness, crude protein, and crude fat (P < 0.05), without affecting moisture, ash, and amino acid composition in LD muscle (P > 0.05). In addition, VA increased catalase (CAT) activity and decreased malondialdehyde (MDA) levels in LD muscle (P < 0.05).Meanwhile, greater levels of CAT and NRF2 mRNA and protein contents with VA treatment were observed in LD muscle (P < 0.05), partly explained by the increased level of RA (P < 0.05). Collectively, our findings indicated that VA injection at birth could improve lamb meat quality by elevating the redness, crude protein, crude fat, and antioxidative capacity in LD muscle of lambs.